Modelling for deriving management plan for production and environment of marine fish cage farm - Woo Sung Jung; Sok Jin Hong; Sang Pil Yoon; Dae In Lee; Won Chan Lee; Dong Myung Kim (Fisheries and Aquatic Sciences)
In South Korea, issues related to production and environmental concerns are arising from marine fish cage farm. To address this, a modeling study was conducted to derive management plan. The model used a combination of hydrodynamic, fish growth, and ecosystem (water quality and sediment) models. The hydrodynamic model utilized Environmental Fluid Dynamics Code. The fish growth model was developed specifically for this study’s purpose. The ecosystem model used was Ecosystem Model for Marine Management. This modelling approach is the first of its kind in South Korea. It incorporated pollution sources such as wasted feed and fish feces as state variables, which were integrated into the ecosystem model. Furthermore, the fish growth model considered fish mortality based on aquaculture conditions (water temperature, dissolved oxygen, stocking density). Although the negative effects of high stocking densities are well-documented, no previous fish modeling cases have considered this. Model validation results showed good reproducibility of annual fish growth and production for each cage. Notably, the model reproduced the phenomenon in the 2-year-olds fish of reduced production per cage followed by an increase due to the consideration of density-dependent mortality. Additionally, spatial and temporal reproducibility of water quality and sediment parameters, including total organic carbon and sedimentation rate, were satisfactory. A limitation of this study remains the lack of sufficient observational data. Scenario analysis for the management plan yielded the following results: Firstly, different age classes require specific management approaches due to varying impacts of feeding, excrement production, and growth-limiting factors. Secondly, optimizing feed input can improve environmental conditions and economic benefits. Thirdly, regulating stocking density is more efficient than adjusting the number of cages. This model provides a tool for deriving management plans for marine fish cage farming based on an integrated understanding of the aquaculture ecosystem. Furthermore, it can be utilized for various purposes, such as assessing the range of influence of organic matter, calculating resting periods for fish farms, and evaluating sustainability.